Religion in Ephesos reconsidered
1 online resource.
Keywords: Religion in Ephesos Reconsidered provides a detailed overview of the current state of research on the most important Ephesian projects offering evidence for religious activity during the Roman period. Ranging from huge temple complexes to hand-held figurines, this book surveys a broad scope of materials. Careful reading of texts and inscriptions is combined with cutting-edge archaeological and architectural analysis to illustrate how the ancient people of Ephesos worshipped both the traditional deities and the new gods that came into their purview. Overall, the volume questions traditional understandings of material culture in Ephesos, and demonstrates that the views of the city and its inhabitants on religion were more complex and diverse than has been previously assumed.